Dynamic analysis of a monopile-supported offshore wind turbine considering the soil-foundation-structure interaction. Issue 158 (July 2022) - Alkhoury, Philip; Soubra, Abdul-Hamid; Rey, Valentine; Aït-Ahmed, Mourad
Abstract: This paper presents a nonlinear dynamic analysis of a large diameter monopile-supported multi-megawatt offshore wind turbine (OWT) installed in sandy soil under perfectly drained conditions. A detailed three-dimensional finite element model was used in the analysis. Two sophisticated soil constitutive models (the critical state elastoplastic SANISAND model and the hypoplastic model with intergranular strain) calibrated on the same Karlsruhe fine sand are adopted. Nonlinear 10-min time-domain simulations are performed within Abaqus/Standard under stochastically simulated scenarios of environmental loadings to compare the OWT structural and geotechnical responses as predicted using the two calibrated soil constitutive models. The comparison shows that both soil models provide close structural responses at the tower top whereas notable discrepancies are observed at mudline and within the soil domain. The relevance of both soil constitutive models was demonstrated via a comparison of their results with those of a conventional elastic-perfectly plastic soil model based on Mohr-Coulomb failure criterion. Finally, this paper investigates the accuracy of two p − y formulations developed for the dynamic analysis of monopiles in sand, based on the presented numerical model. Highlights: Nonlinear dynamic simulations of a monopile-supported offshore wind turbine (OWT) are performed. A 3D FE model which explicitly considers the OWT superstructure and the soil-foundation interaction is developed. The OWT dynamic responses obtained using two calibrated advanced sand constitutive models are compared. The suitability of two existing p − y formulations for the dynamic analysis of OWTs is examined.